MOB1 deletion in murine mature adipocytes ameliorates obesity and diabetes - Miki Nishio; Keiko Yamaguchi; Junji Otani; Katsuya Yuguchi; Daisuke Kohno; Tsutomu Sasaki; Tadahiro Kitamura; Masakazu Shinohara; Tomoyoshi Soga; Koichi Kawamura; Atsuo T. Sasaki; Masashi Oshima; et al. (Proceedings of the National Academy of Sciences, 2025)
There is currently a global epidemic of obesity and obesity-related diseases such as type 2 diabetes due to decreased physical activity, excessive food intake, and/or genetic predisposition. The Hippo-YAP1 pathway has attracted attention as a potential therapeutic target because YAP1/TAZ activation in murine immature adipocytes in vitro suppresses their differentiation by inhibiting PPARγ activity. However, the role of YAP1 activation in mature adipocytes in vivo remains unclear. MOB1, whose expression is increased in obesity, is the hub of the Hippo core molecule complex and negatively regulates YAP1/TAZ activation. Therefore, we generated aMob1DKO mutant mice, which feature deficiency of Mob1a/b specifically in mature adipocytes. Compared to controls, aMob1DKO mice subjected to a high-fat diet showed beneficial changes consistent with resistance to diet-induced obesity. The mutants exhibited increases in basal lipolysis, “beiging,” and energy expenditure, as well as suppression of ROS production and inflammation in white adipose tissue. Insulin sensitivity and glucose tolerance were improved, and ectopic fat accumulation was reduced. Most of these changes were dependent on the YAP1 activation observed in mature white adipose tissue of aMob1DKO mice. FGF21, which improves lipid metabolism, was upregulated directly via YAP1 activation, and many of the phenotypes seen in aMob1DKO mice were also dependent on FGF21. Thus, the aMob1DKO mouse is an interesting model for the study of the metabolic effects of diet-induced obesity and protection against diabetes. Our work suggests that a YAP1-FGF21 axis exists in adipocytes that may be a potential therapeutic target for obesity.